Localização e navegacão de um robô móvel omnidirecional: caso de estudo da competição robot@factory - Costa, Paulo Gomes da (2017)
The Robot@Factory competition, was recently included in Robotica, the main Robotics Portuguese Competition. This robot competition takes place in an emulated factory plant, where Automatic Guided Vehicles (AGVs) must cooperate to perform tasks. To accomplish their goals the AGVs must deal with localization, navigation, scheduling and cooperation problems, that must be solved autonomously. The presented robot competition can play an important role in education due to the inherent multi-disciplinary concepts that are involved,motivating students to technological areas. It also plays an important role in research and development, because it is expected that the outcomes that will emerge here, will later be transfered to other application areas, such as service robots and manufacturing. By presenting a scaled down factory shop floor, this competition creates a benchmark that can be used to compare different approaches to the problems that arise on this kind of environments. Also, the ability, in some restricted areas, to alter the environment, can promote the test and evaluation of different localization mechanisms, something that is usually, more restricted in other competitions, opening this area to be explored and benchmarked. In this paper it is discussed one of the possible approaches, that can be applied to the robot competition, serving as reference to the actual and new potential participating teams.